(untitled) (London Journal of Medical and Health Research, 2025)
Oncology is the study of cancer cells. To understand oncology is to understand the biology of cells. To do this is to understand how the cells work. There are several ways to get to the right research: Next Generation Sequencing or (NGS) is a powerful tool used in genomics research. NGS can sequence millions of DNA fragments at once, providing detailed information about the structure of genomes, genetic variations, gene activity, and changes in gene behavior. Targeted therapies are a type of cancer treatment that targets proteins that control how cancer cells grow, divide, and spread. Personalized treatment is to provide help for the patient to deal with cancer issues.